Accessory nerve palsy. Issue 11 (November 1977) - Olarte, M; Adams, D
Abstract : After apparently uncomplicated excision of benign lesions in the posterior cervical triangle, two patients had shoulder pain. In one, neck pain and trapezius weakness were not prominent until one month after surgery. Inability to elevate the arm above the horizontal without externally rotating it, and prominent scapular displacement on arm abduction, but not on forward pushing movements, highlighted the trapezius dysfunction and differentiated it from serratus anterior weakness. Spinal accessory nerve lesions should be considered when minor surgical procedures, lymphadenitis, minor trauma, or tumours involved the posterior triangle of the neck.